ANTARA PERSEPSI DAN PENGARUH LINGKUNGAN TERDEKAT, FAKTOR PENENTU KONSUMEN PADA PEMBELIAN SEPEDA MOTOR “HONDA” - Andri Nurtantiono; Ismail Marzuki; Aditya Chinintyawan Kayohakicky; Maruti Oktalina (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study was to analyze the influence of family, reference groups and perceptions on purchasing decisions for Honda motorcycles in Surakarta City. This research approach uses quantitative research methods, in the form of empirical research with the object of the people of Surakarta City who have Honda motorcycles with 128 respondents as the research sample. All hypotheses in this study were proven, namely that either partially or simultan the Family, Reference Groups and Perceptions Variables had a significant positive effect on purchasing decisions. Perception Variables become the dominant variable influencing the Purchase Decision. Keywords : Purchase Decision, Family, Reference Group, Perception